Reversal of Gender Gaps in Child Development: Evidence from Young Children in India - Florencia López Bóo; Maria Eugenia Canon (Institute for the Study of Labor (IZA), 2014)
This paper provides unique evidence of a reversal of gender gaps in cognitive development in early childhood. We find steep caste and gender gradients and few substantive changes once children enter school. The gender gap, however, reverses its sign for the upper caste, with girls performing better than boys at age 5 but thereafter following the general pattern in India of boys performing better.
Keywords: I2; J1; J7; 330; cognitive skills; India; gender; caste inequality; children; Oaxaca